Ownership structure of IPO firms in Singapore and its implications on underpricing - Tan, Jasmine Lay Khim (2008)
In this paper, we examine how ownership structure affects underpricing from the year 1990 to 2002 by focusing on two aspects of the ownership structure – Pre-IPO (Initial Public Offering) ownership stakes and ownership concentration. Our results show that indeed, pre-IPO ownership stakes does affect underpricing.